دراسة تأنثير مياه الري الممغنطة على إنتاجية محصول البطاطا صنف سبونتا في منطقة وادي سوف - البشير سبع; علي منصوري; محمد العيد العابد (جامعة الوادي - university of eloued, 2024)
This study was completed in the municipality of Hassi Khalifa, which aims to use magnetic technology to treat underground well water, which is characterized by high salinity, and to determine its suitability in the process of watering the potato crop, the Spunta variety, known for its wide spread in the Wadi Souf region. This study included a focus on the characteristics The productivity of this crop, which is based on pivotal spraying in the irrigation process, and through analyzing the product and conducting a comparison process on a set of features between replicates irrigated with magnetized water and those irrigated with non-magnetized water, shows the following: -The average number of tubers in plants watered with magnetized water was greater compared to plants watered with non-magnetized water, and the average number of standard tubers, which is intended for tubers that weighed more than (40 grams), as the results showed that there was a greater number of standard tubers in plants watered with magnetized water compared to irrigated plants. With non-magnetized water. The average tuber weight (g) was compared between watered with magnetized water and non-magnetized water, where the superiority was for watered with magnetized water like the previous comparisons, and this result also included the average weight of the standard tuber for plants watered with magnetized water and non-magnetized water. In terms of the average production per plant (g), the values for the magnetized water were greater than the values for the non-magnetized water. As for the production per hectare, it was estimated that the two replicates watered with the magnetized water were more productive compared to the plants watered with the non-magnetized water. In the process of comparing the standard production per hectare, it gave The calculations that were carried out showed a clear agreement for plants watered with magnetized water compared to those watered with non-magnetized water. The tuber composition of production was varied, as in weights less than (300 grams) the advantage was for plants watered with non-magnetic water. On the contrary, in tubers larger than (300 grams), the proportions were in favor of plants watered with magnetized water.
التنوع الحيوي وفيزيولوجيا النبات
Keywords: magnetic technology - magnetic water - pivot spray - two repeats - tuber composition